Management of Familial Adenomatous Polyposis in Children and Adolescents: Position Paper From the ESPGHAN Polyposis Working Group. Issue 3 (March 2019) - Hyer, Warren; Cohen, Shlomi; Attard, Thomas; Vila-Miravet, Victor; Pienar, Corina; Auth, Marcus; Septer, Seth; Hawkins, Jackie; Durno, Carol; Latchford, Andrew
Abstract : ABSTRACT: Familial adenomatous polyposis (FAP) is a well-described inherited syndrome, characterized by the development of hundreds to thousands of adenomas in the colorectum, with implications in children and adolescents. Almost all adult patients will develop colorectal cancer if they are not identified and treated early enough. Identifying and screening for FAP commences in adolescence. The syndrome is inherited as an autosomal dominant trait and caused by mutations in the adenomatous polyposis ( APC ) gene. This European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) position paper provides a guide for diagnosis, assessment, and management of FAP in children and adolescents. This is the first position paper regarding FAP published by ESPGHAN. Literature from PubMed, Medline, and Embase was reviewed and in the absence of evidence, recommendations reflect the opinion of paediatric and adult experts involved in the care of polyposis syndromes. Because many of the studies that form the basis for the recommendations were descriptive and/or retrospective in nature, these of the recommendations are supported on expert opinion. This position paper will instruct on the appropriate management and timing of procedures in children and adolescents with FAP.